Posture control development in children aged 2–7 years old, based on the changes of repeatability of the stability indices - Sobera, Małgorzata; Siedlecka, Bożena; Syczewska, Małgorzata (Neuroscience letters, 2011)
▶ Repeatability of posture control indices improves with age in young children. ▶ Differences of the left and right foot reflect the development of lateralization. ▶ Posture control of children can be assessed on the basis of velocity index. ▶ Ellipse area is good to describe the lateralization of leg in the support function. One of the most common problems encountered in posture control studies is relatively poor repeatability of postural stability measures based on the COP (center of pressure) time-series which results from the inherent variability of postural control. The repeatability of the data reflecting the postural control mechanisms in young children is still not well enough explained. The differences between of the repeatability of the stability indices of left and right foot may reflect the lateralization development of legs in the support function. The aim of the present study was two-fold: the assessment of the repeatability of the stability indices in three consecutive trials in young children, aged 2–7 years old, during quiet bipedal stance and the description of process of lower limbs lateralization, based on the difference of repeatability of both feet stability the indices changing with years. The subjects were 272 young healthy children aged 2–7 years old separated in 6 groups for children of different age. Each child stood for around 90 s on two AccuSway force platforms (AMTI). The shifts of COP beneath left and right legs were recorded onto a computer by using appropriate software compatible with platforms. The indices of the ellipse area and velocity COP shifts were calculated. For assessment of the repeatability the concordance correlation coefficient (CCC) of the indices was used between the 1st and 2nd, 2nd and 3rd, and 1st and 3rd trials. Young children of 2–4 years old exhibit low level of the stability indices repeatability which increases in 5-year-old children, 6-year-olds revealed both low and high and 7-year-olds good and high levels of repeatability. Youngest children showed higher repeatability of the ellipse area of the left leg, 3- and 4-year-olds the right leg, while 6-year-olds again the left leg. In 5- and 7-year-olds there were no differences in the repeatability of stability indices between the left and right foot. The comparisons of the repeatability of the velocity index between the left and right leg revealed the difference only in 3 years old children. Posture control development of children can be assessed on the basis of velocity index but the COP ellipse area index is better way to describe the lateralization process. The repeatability of the stability indices is poor from 2 to 4 year of life but increases significantly from 5 to 7 year of life. The comparisons of repeatability between the left and right foot indices reflect the developmental process of lateralization of lower limbs in the support function and reveal that the left lower leg is a dominant one in support function while standing position. The process of leg lateralization is finishing about 6th year of life.